Educational Outcomes for Students with Special Needs: The Impact of Support and Resources on Teachers’ Perceptions - Sharpe, Traci Y. (Journal of the American Academy of Special Education Professionals, 2013)
This article defines a theoretical framework for reviewing factors that affect a teacher’s self-efficacy as they work to impact the educational outcomes for students with special needs. Bandura’s Social-Cognitive Theory is utilized on the basis that one’s belief in his ability to be effective has a direct impact on his effectiveness. This information will contribute greatly to the field of education and the work of administrators who seek answers for increasing teachers’ self-efficacy as society continues to move toward the inclusion of those with disabilities.